On the Age and Origin of Lake Ejagham, Cameroon, and Its Endemic FishesAbstract - Curt Stager, Jay; Alton, Kenneth; Martin, Christopher H.; King, David T.; Petruny, Lucille W.; Wiltse, Brendan; Livingstone, Daniel A. (Quaternary Research, 2018)
Lake Ejagham is a small, shallow lake in Cameroon, West Africa, which supports five endemic species of cichlid fishes in two distinct lineages. Genetic evidence suggests a relatively young age for the species flocks, but supporting geologic evidence has thus far been unavailable. Here we present diatom, geochemical, mineralogical, and radiocarbon data from two sediment cores that provide new insights into the age and origin of Lake Ejagham and its endemic fishes. Radiocarbon ages at the base of the longer core indicate that the lake formed approximately 9 ka ago, and the diatom record of the shorter core suggests that hydroclimate variability during the last 3 millennia was similar to that of other lakes in Cameroon and Ghana. These findings establish a maximum age of ca. 9 cal ka BP for the lake and its endemic species and suggest that repeated cichlid speciation in two distinct lineages occurred rapidly within the lake. Local geology and West African paleoclimate records argue against a volcanic, chemical, or climatic origin for Lake Ejagham. Although not conclusive, the morphometry of the lake and possible signs of impact-induced effects on quartz grains are instead more suggestive of a bolide impact.
Keywords: Africa; cameroon; Cichlid; Diatom; evolution; Lake Ejagham; Speciation; West African monsoon

Climate variability and cultural eutrophication at Walden Pond (Massachusetts, USA) during the last 1800 years - Stager, J. Curt; Wiltse, Brendan; Hubeny, J. Bradford; Yankowsky, Eric; Nardelli, David; Primack, Richard (PLOS ONE, 2018)
Recent shifts in the ecological condition of Walden Pond, MA, are of potentially wide interest due to the lake's importance as a cultural, historical, and recreational resource in addition to its scientific value as an indicator of local and global environmental change. Algal microfossils in six sediment cores document changes in hydroclimate and trophic status of the lake during the last 1800 years and extend two previous sediment core records of shorter length. Low percentages of planktonic diatoms in the longest cores (WAL-3, WAL-15) indicate shallowing and/or greater water clarity associated with a relatively arid interval during the Medieval Climate Anomaly, ca. A.D. 1150-1300, Cultural eutrophication of the lake since the A.D. 1920s caused diatoms in the genera Asterionella and Synedra to increase in relative abundance at the expense of Cyclotella, Discostella, and the chrysophyte alga Mallomonas allorgel. Percentages of Asterionella and Synedra have remained fairly stable since A.D. 2000 when a previous sediment core study was conducted, but scaled chrysophytes have become more numerous. These findings suggest that, although mitigation efforts have curtailed anthropogenic nutrient inputs to Walden Pond, the lake has not returned to the pre-impact condition described by Henry David Thoreau and may become increasingly vulnerable to further changes in water quality in a warmer and possibly wetter future.
Keywords: BOREAL LAKES; canada; CRAWFORD LAKE; DEPTH MODELS; ENVIRONMENTAL-CHANGE; ice-age; new-england; NORTH-AMERICA; NORTHEASTERN UNITED-STATES; organic-matter